PENGARUH PEMANFAATAN INTERNET DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS VII DI SMP NEGERI 1 KAPONGAN TAHUN PELAJARAN 2015/2016 - Irma Noervadila (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2016)
Student learning outcomes are achieved vary, there are students who are high achievers, medium, and there are also students who are underachieving. This is of course influenced by various factors, both internal factors (derived from the students themselves) as well as external factors (derived from outside the students themselves). Factors that affect student achievement arise from within and outside the student is learning motivation and learning styles of students. Habit or something that is done repeatedly is a way of acting that has been mastered, tested, uniform, and applies automatically without thinking anymore, which can affect students' goals to achieve the desired learning outcomes. This study aims to determine whether there is influence of the use of the internet and motivation toward learning outcomes seventh grade students of SMP Negeri 1 Kapongan regency. This research is quantitative. Methods of data collection were questionnaires, tests, and documentation. The subjects were students of class VII with a population of 127 respondents using the random sampling method was taken by 100 respondents. Analysis of data using correlation analysis and multiple regression analysis. Hypothesis test to determine the influence of independent learning, and the learning environment is known F reg at 34.052. While F table that is equal to 3.96 with a significance level of 5%. From these calculations, the prices of 34.052 F reg greater than F table the 5% significance level of 3.96. So F reg> F table which means the null hypothesis is rejected and the alternative hypothesis is accepted. This suggests that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. An alternative hypothesis is accepted: "There is a very strong significant effect between use of the Internet, intrinsic motivation and extrinsic motivation together on learning outcomes of students of SMP Negeri 1 Kapongan 2015/2016 school year. For R Square obtained 51.553%. From the calculation of the analysis can be seen that extrinsic motivation is greater than the other variables which give the effect of 33.598% of the student learning outcomes. Influence of intrinsic motivation of 23.117%, while the use of the Internet provide a donation of 17.975.